Hybrid breeding and cultivar diversity in rice production in China. Issue 1 (10th May 2022) - Huang, Min
Abstract: This study determined the effect of hybrid breeding on cultivar diversity in rice ( Oryza sativa L.) production in China. The results showed that hybrid breeding led to increases in the Shannon index of cultivar diversity by 29–184% during the period 2011–2015 compared with the period 1986–1990 for 10 major hybrid rice‐producing provinces in China. There was a significant exponential relationship between the Shannon index of cultivar diversity and the number of hybrid cultivars and the total number of cultivars across the 10 provinces and the two 5‐yr periods. The results of this study also demonstrate that hybrid rice breeding resulted in a cultivar diversity that came close to saturation in some provinces, such as Anhui, Hunan, Jiangxi, and Sichuan, and highlight the urgent need for a reconsideration of the development of hybrid rice industrialization in China to avoid wasting resources caused by overbreeding. CORE IDEAS: Hybrid breeding significantly increased rice cultivar diversity in China. Rice cultivar diversity came close to saturation in some provinces in China. A reconsideration of the development of hybrid rice industrialization is needed in China.